ANONIMITAS VISUAL DAN PENEKANAN VERBAL: Tinjauan Semiotika Konten Instagram BNN Cegah Narkoba - Habibi, Muhamad Lutfi; Mahbubah, Putri Sekar Giri Fatimah (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2024)
The success of the Badan Narkotika Nasional (BNN) in protecting and saving the Indonesian people from stopping illegal drug trafficking in 2021 has exceeded the target set. This can be realized thanks to preventive campaigns, including Instagram social media. This research aims to present the results of a semiotic analysis of visual content uploaded by BNN via the BNN Cegah Narkoba Instagram account (@bnn_cegahnarkoba) from January to June 2022 based on their success in reducing the rate of triggering and illicit circulation of drugs in Indonesia throughout 2021. The method used in this study is the triadic semiotic analysis by Charles Sanders Peirce, who interprets the relationship between objects through DKV elements, DKV principles, and typography in contents with a representamen that produces an interpretant. The results of this research show that the meaning of the BNN Cegah Narkoba’s campaign content tends to display anonymous visual representations of its audience and places more emphasis on preventive verbal messages. Additionally, visual associations to symbols of popular fictional characters are also used so that the range of impact can be even wider. This tendency is carried out based on compliance with media ethics and consideration of the target audience dominated by young people. Keywords: anti-drug campaign, BNN, Peirce’s semiotics